2008
DOI: 10.1007/s00134-008-1284-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial comparing ocular lubricants and polyacrylamide hydrogel dressings in the prevention of exposure keratopathy in the critically ill

Abstract: Our data suggest that Geliperm is as effective as Lacrilube in the prevention of exposure keratopathy in the critically ill. We also note that nursing staff must be fully trained in its application for eye care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…Several studies have been reported that compare different methods of eye protection in ICU patients [16,[21][22][23][24] or describe algorithms to follow in the ICU [17,25], but it appears that such protocols are not always followed [25] in many units, including our ICU.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have been reported that compare different methods of eye protection in ICU patients [16,[21][22][23][24] or describe algorithms to follow in the ICU [17,25], but it appears that such protocols are not always followed [25] in many units, including our ICU.…”
Section: Discussionmentioning
confidence: 98%
“…A patient was considered to have exposure keratopathy if any eye had a grade greater than 0. Chemosis was graded as either no edema (1), edema without dellen (2), or edema with dellen (3) (modified from Ezra et al [16]). Lagophthalmos was graded as lids opposed (1), conjunctiva visible (2), or cornea visible (3) [17].…”
Section: Methodsmentioning
confidence: 99%
“…Unconscious or sedated patients must be provided with eye care every 2 hours (cleaning with gauze and saline and administration of a specific ocular lubricant). Ezra et al (2009) There was no statistically significant difference in the prevention of corneal complications between the group Lacrilube ® (ointment) and Geliperm ® (adhesive film).…”
Section: Author(s)/year Main Resultsmentioning
confidence: 92%
“…The authors suggested that this result was due to lack of proper training to use this method (Ezra et al, 2005). The same authors developed another study (Ezra, Chan, Solebo, Malik, Crane, Coombes, & Healy, 2009) in 2009, also with recommendation degree B and evidence level II, where they proved there is no statistically significant difference in preventing corneal complications between the group Lacrilube ® and Geliperm ® .…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…A similar UK study did not show any significant difference between the ocular lubricants (Lacrilube) and polyacrylamide gel (Geliperm) in preventing exposure keratopathy in the critically ill 12. The authors emphasise that nursing staff must be trained in the application of polyacrylamide gel for eye care.…”
Section: Management Of Ocular Exposurementioning
confidence: 81%